N6-benzyladenosine derivatives as novel N-donor ligands of platinum(II) dichlorido complexes - Starha, Pavel; Popa, Igor; Trávníček, Zdeněk; Vančo, Ján (Molecules (Basel, Switzerland), 2013)
The platinum(II) complexes trans-[PtCl₂(Ln)₂]∙xSolv 1-13 (Solv = H₂O or CH3OH), involving N6-benzyladenosine-based N-donor ligands, were synthesized; L(n) stands for N6-(2-methoxybenzyl)adenosine (L₁, involved in complex 1), N6-(4-methoxy-benzyl)adenosine (L₂, 2), N6-(2-chlorobenzyl)adenosine (L₃, 3), N6-(4-chlorobenzyl)-adenosine (L₄, 4), N6-(2-hydroxybenzyl)adenosine (L₅, 5), N6-(3-hydroxybenzyl)-adenosine (L₆, 6), N6-(2-hydroxy-3-methoxybenzyl)adenosine (L₇, 7), N6-(4-fluoro-benzyl)adenosine (L₈, 8), N6-(4-methylbenzyl)adenosine (L₉, 9), 2-chloro-N6-(3-hydroxy-benzyl)adenosine (L₁₀, 10), 2-chloro-N6-(4-hydroxybenzyl)adenosine (L₁₁, 11), 2-chloro-N6-(2-hydroxy-3-methoxybenzyl)adenosine (L₁₂, 12) and 2-chloro-N6-(2-hydroxy-5-methylbenzyl)adenosine (L₁₃, 13). The compounds were characterized by elemental analysis, mass spectrometry, IR and multinuclear (¹H-, ¹³C-, ¹⁹⁵Pt- and ¹⁵N-) and two-dimensional NMR spectroscopy, which proved the N7-coordination mode of the appropriate N6-benzyladenosine derivative and trans-geometry of the title complexes. The complexes 1-13 were found to be non-toxic in vitro against two selected human cancer cell lines (HOS and MCF7; with IC₅₀ > 50.0 µM). However, they were found (by ESI-MS study) to be able to interact with the physiological levels of the sulfur-containing biogenic biomolecule L-methionine by a relatively simple 1:1 exchange mechanism (one L(n) molecule was replaced by one L-methionine molecule), thus forming a mixed-nitrogen/sulfur-ligand dichlorido-platinum(II) coordination species.
Keywords: benzylové sloučeniny; Purines; protinádorové látky; ligandy; Cell Line, Tumor; Kinetin; Ligands; Organoplatinum Compounds; puriny; Mass Spectrometry; Inhibitory Concentration 50; Benzyl Compounds; lidé; Humans; nukleární magnetická rezonance biomolekulární; inhibiční koncentrace 50; hmotnostní spektrometrie; nádorové buněčné linie; organoplatinové sloučeniny; Antineoplastic Agents; Nuclear Magnetic Resonance, Biomolecular; kinetin